RETRACTED: The effective organization of customer service technology in freight transportation sector - Kobulov Jamshid; Barotov Jamshid; Samiev Farrukh; Fayzullaev Gaybullo (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001